A UK feasibility and validation study of the VE1 monoclonal antibody immunohistochemistry stain for BRAF-V600E mutations in metastatic melanoma - Lo, Michelle Chin I (Br J Cancer, 2016)
BACKGROUND: Determining the BRAF mutation status of patients with advanced metastatic melanoma is essential in order to assess patients' eligibility for targeted BRAF inhibitor therapy. The aim of this study was to validate the utility of immunohistochemistry (IHC) to rapidly obtain the BRAF status in the UK cancer centre setting. METHODS: All samples sent for molecular testing for detection of the BRAF mutation over a 26-month period were prospectively tested using the VE1 monoclonal antibody IHC stain. RESULTS: Two-hundred and nineteen samples from 214 patients were identified. All patients were AJCC stage III/IV, except one. There was an overall 95.0% (208/219) concordance rate, with a sensitivity of 94.4% (84/89) and a specificity of 95.4% (124/130) when using genomic assays as the gold standard. Discordance resulted from the inability of the molecular technique to detect the V600E2 mutation and an inability of the IHC staining technique to detect non-V600E mutations. Molecular testing on smaller tumour deposits was also unreliable. CONCLUSIONS: IHC staining has good sensitivity and excellent specificity for BRAF V600E mutations. BRAF IHC can be incorporated into a BRAF mutation testing algorithm for UK cancer centres to as a feasible first-line assay and identify a subset of cases that require subsequent genomic testing. It has the additional major advantages of reduced cost and rapid turnaround time.